2017
DOI: 10.1002/aic.15743
|View full text |Cite
|
Sign up to set email alerts
|

Fe‐Beta@CeO2 core‐shell catalyst with tunable shell thickness for selective catalytic reduction of NOx with NH3

Abstract: A series of core-shell structural deNO x catalysts using small-grain Beta supporting FeO x nanoparticles as the core and tunable CeO 2 thin film thickness as sheaths were designed and controllably synthesized. Their catalytic performances were tested for selective catalytic reduction of NO x with NH 3 (NH 3 -SCR). It was found that CeO 2 shell thickness plays an important role in influencing the acidity and redox properties of the catalysts. Fe-Beta@CeO 2 core-shell catalysts exhibit excellent resistance to H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 57 publications
0
7
2
Order By: Relevance
“…The TOF value is a function of conversion, molar flow rate, and catalyst amount. However, this would not provide a good prediction of activity if the dispersion of the element is uneven . The TOF value reported by Pd/CeO 2 is 1.459×10‐3 s −1 , which is smaller than other materialization based catalysts prepared in current work (Table ).…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…The TOF value is a function of conversion, molar flow rate, and catalyst amount. However, this would not provide a good prediction of activity if the dispersion of the element is uneven . The TOF value reported by Pd/CeO 2 is 1.459×10‐3 s −1 , which is smaller than other materialization based catalysts prepared in current work (Table ).…”
Section: Resultscontrasting
confidence: 55%
“…However, this would not provide a good prediction of activity if the dispersion of the element is uneven. [85] The TOF value reported by Pd/CeO 2 is 1.459 × 10-3 s À 1 , which is smaller than other materialization based catalysts prepared in current work ( Table 6). The Pd/CeO 2 À MgO (3 : 1) catalyst showed higher TOF value in all the reported temperature ranges which proved it a better combination of the supported catalyst.…”
Section: Effect Of Supports Materializationcontrasting
confidence: 52%
“…Nitrogen oxides (NO x ) emitted by industrial processes are crucial atmospheric pollutants, which affect the global environment and endanger human's health 1,2 . Thereby, the reduction of NO x to harmless N 2 is an important task for environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…Various group reported core-shell structure containing nanocatalyst with unique physical and chemical interaction provide result in synergetic effect. [21] M. Cargnello et al developed Pd@CeO 2 /Al 2 O 3 which showed better catalytic activity than either Pd/CeO 2 or Pd/CeO 2 /Al 2 O 3 for methane combustion due to interfacial interaction present in core-shell nanocatalyst. [22] C. Wang et al prepared Ni@ graphene composite, the outer shell prevents the inner Ni nanoparticles being etched in presence of air and oxidant H 2 O 2 .…”
mentioning
confidence: 99%
“…The HRTEM of Fe 3 O 4 @Fe-CeO 2 /Ag nanocatalyst revealed that Fe 3 O 4 is coated with spherical cerium oxide, therefore resulting Fe 3 O 4 @Fe-CeO 2 core-shell structure. [21,27,35,37] The subsequent incorporation of Ag results in the surface decoration of Fe 3 O 4 @Fe-CeO 2 spheres (Figure 1). This nanostructure composite was further characterized by EDAX analysis which confirms the presence of Fe, Ce, Ag and O elements in Fe 3 O 4 @Fe-CeO 2 /Ag.…”
mentioning
confidence: 99%